Effect of extraction methods on yield, total phenolic content, antioxidant, and anti-tyrosinase properties of combretum indicum leaves - Thanaseelan, Tanesha; Nur Aina Raihana, Muhamad Yusuff; Kutty, Rajaletchumy Veloo (The Malaysian Analytical Sciences Society, 2024)
Plants form a natural source of key bioactive chemicals equipped with excellent antioxidant and anti-tyrosinase properties. The restorative plant Combretum indicum (C. indicum), which belongs to the Combretaceae family, was widely used in customary treatment in the past. The target of this study is to assess the effects of water as a solvent, traditional extraction strategies (maceration and Soxhlet extraction), and extraction time on C. indicum yield. The total phenolic content (TPC), as well as antioxidant and tyrosinase inhibitory activities, were observed by utilising an ultraviolet-visible spectrophotometer. DPPH radical scavenging was used to determine the antioxidant property, while a mushroom tyrosinase inhibition assay was utilised to evaluate the anti-tyrosinase activity. Maceration carried out for 72 h showed good outcomes for TPC, antioxidant, and anti-tyrosinase activities. The results showed that TPC, antioxidant assay, and anti-tyrosinase activities had a significant linear correlation (p <0.05). It is evident from the study that C. indicum leaves, which contain numerous phytochemicals, are strong antioxidants and tyrosinase inhibitors that can potentially play a significant role in the pharmaceutical and cosmetic industries.